Utilization of Pharmacokinetic/Pharmacodynamic Modeling in Pharmacoepidemiological Studies: A Systematic Review on Antiarrhythmic and Glucose-Lowering Medicines - Mohammadi Jouabadi, Soroush; Nekouei Shahraki, Mitra; Peymani, Payam; Stricker, Bruno H.; Ahmadizar, Fariba (Frontiers in Pharmacology, 2022)
Introduction: In human pharmacology, there are two important scientific branches, i.e., clinical pharmacology and pharmacoepidemiology. Pharmacokinetic/Pharmacodynamic (PK/PD) modeling is important in preclinical studies and randomized control trials. However, it is rarely used in pharmacoepidemiologic studies on the effectiveness and medication safety where the target population is heterogeneous and followed for longer periods. The objective of this literature review was to investigate how far PK/PD modeling is utilized in observational studies on glucose-lowering, and antiarrhythmic drugs. Method: A Systematic Literature search of MEDLINE, EMBASE, and WEB OF SCIENCE was conducted from January 2010 to 21st February 2020. To calculate the utilization of PK/PD modeling in observational studies, we followed two search strategies. In the first strategy, we screened a 1% random set from 95,672 studies on glucose-lowering and antiarrhythmic drugs on inclusion criteria. In the second strategy, we evaluated the percentage of studies in which PK/PD modeling techniques were utilized. Subsequently, we divided the total number of included studies in the second search strategy by the total number of eligible studies in the first search strategy. Results: The comprehensive search of databases in addition to the manual search of included references yielded a total of 29 studies included in the qualitative synthesis of our systematic review. Nearly all 29 studies had utilized a PK model, whereas only two studies developed a PD model to evaluate the effectiveness of medications. Sixteen out of 29 studies (55.1%) used a PK/PD model in the observational setting to study effect modification. The utilization of PK/PD modeling in observational studies was calculated as 0.42%. Conclusion: PK/PD modeling techniques were substantially underutilized in observational studies of antiarrhythmics and glucose-lowering drugs during the past decade.